2011
DOI: 10.1080/07359683.2011.545337
|View full text |Cite
|
Sign up to set email alerts
|

Nonbranded or Branded Direct-to-Consumer Prescription Drug Advertising—Which is More Effective?

Abstract: Recently, pharmaceutical manufacturers have increased the amount of nonbranded, disease-education focused, direct-to-consumer advertisements. A comparison to branded, product-specific, ads was examined through a series of survey questions measuring consumer attitudes and the role of involvement. Nonbranded ads compared favorably to branded ads and should remain a viable part of the marketing mix. Consumers' level of disease state involvement was the strongest determinant of attitudes overall and within the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…As endorsers play a key role within the experimental setting, we used a narrative instead of a statistical approach for designing the message statement (Hinyard and Kreuter, 2007). In addition, as non-branded DTCA, which focus on disease and health education instead of highlighting a particular drug or device, compared favorably to branded ads, we took a non-branded advertisement (Rollins et al, 2011). The advertising statement consisted of three paragraphs: introduction, impacts of diabetes, and recommendation.…”
Section: Research Methodology Experimental Design and Proceduresmentioning
confidence: 99%
“…As endorsers play a key role within the experimental setting, we used a narrative instead of a statistical approach for designing the message statement (Hinyard and Kreuter, 2007). In addition, as non-branded DTCA, which focus on disease and health education instead of highlighting a particular drug or device, compared favorably to branded ads, we took a non-branded advertisement (Rollins et al, 2011). The advertising statement consisted of three paragraphs: introduction, impacts of diabetes, and recommendation.…”
Section: Research Methodology Experimental Design and Proceduresmentioning
confidence: 99%
“…It was assessed with a one-item, dichotomous choice option (yes=no) coded as 1 (look for more information now) and 2 (do not look for more information now). This single item ISB measurement has been used in prior DTC research and demonstrated equivalence to multiple item measures (Bergkvist & Rossiter, 2007;Rollins, 2010;Rollins, King, Zinkhan, & Perri, 2011). SAS Version 9.1 was used for data analysis.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While the link between behavioral intentions and actual behavior is controversial and difficult to predict, behavioral intentions and past behavior are the most logical and researched proxies for behavior prediction. Recent research in DTC prescription drug advertising has shown those with higher behavioral intentions perform the desired behavior significantly more (Rollins et al, 2010(Rollins et al, , 2011. Further, in addition to sales analysis and ad recall, advertising effectiveness has been measured using two primary constructs, attitude toward the ad (A AD ) and attitude toward the brand (A B ).…”
Section: Information Search Intent?mentioning
confidence: 99%
“…It was assessed with a one-item, dichotomous choice option (yes/no) coded as 1 ¼ "look for more information now" and 2 ¼ "do not look for more information now". This single item ISB measurement scale has been used in prior DTC research and demonstrated equivalence to multiple item measures (Bergkvist and Rossiter, 2007;Rollins et al, 2010Rollins et al, , 2011.…”
Section: Information Search Intent (Isi)mentioning
confidence: 99%